Respuesta :

For this case we must find an expression equivalent to:

[tex]\sqrt [7] {x} * \sqrt [7] {x} * \sqrt [7] {x}[/tex]

By definition of properties of powers and roots we have:

[tex]\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}[/tex]

So, rewriting the given expression we have:

[tex]x ^ {\frac {1} {7}} * x ^ {\frac {1} {7}} * x ^ {\frac {1} {7}} =[/tex]

To multiply powers of the same base we put the same base and add the exponents:

[tex]x ^ {\frac {1} {7} + \frac {1} {7} + \frac {1} {7}} =\\x ^ {\frac {3} {7}}[/tex]

Answer:

Option 1

Answer: Option 1.

Step-by-step explanation:

We need to remember that:

[tex]\sqrt[n]{a^m}=a^{\frac{m}{n}}[/tex]

Then, having the expression:

[tex]\sqrt[7]{x}*\sqrt[7]{x} *\sqrt[7]{x}[/tex]

We can rewrite it in this form:

[tex]=x^{\frac{1}{7}}*x^{\frac{1}{7}} *x^{\frac{1}{7}}[/tex]

According to the Product of powers property:

[tex](a^m)(a^n)=a^{(m+n)}[/tex]

Then, the simplied form of the given expression, is:

[tex]=x^{(\frac{1}{7}+\frac{1}{7}+\frac{1}{7})}=x^\frac{3}{7}[/tex]

ACCESS MORE